Uv setting ceramic slurry for battery pole piece, preparation method thereof and preparation method of battery pole piece
Patent Information
- Application Number
- CN202411812512.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-12-10
AI Technical Summary
[0006]存在问题:涂陶垫片改进后浆料与陶瓷在出模头时水平压力无干扰,但湿膜进入烤箱后受风刀影响依旧存在扩散问题;对涂布机上风嘴结构进行改造后挡块结构可能造成边缘料区干燥不均问题
[0028] 1) Fast setting: Utilizing UV surface curing film-forming technology, the surface curing of ceramic slurry can be completed within 3 seconds. The ceramic setting can be completed before or in the early stage of oven curing, which can effectively solve the problem of ceramic diffusion.
Smart Images

Figure CN119614024B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a UV-cured ceramic slurry for battery electrodes and its preparation method, as well as a method for preparing battery electrodes. Background Technology
[0002] Lithium-ion batteries have seen rapid development in recent years. With technological advancements, researchers have conducted in-depth studies on battery safety performance. Adding ceramic coatings to both sides of the electrode coating significantly improves cell safety. However, since the slurry and ceramic share the same solvent system, diffusion inevitably occurs upon contact. Furthermore, the diffusion at the transition from wet to dry film is uncontrollable, leading to frequent and ineffective adjustments by on-site staff. This affects coating dimensions and subsequent CCD recognition, posing a potential safety hazard to the cell.
[0003] Currently, by adjusting the oven parameters and using a high-temperature, low-air mode in the first few sections, the ceramic is shaped in the preheating section, reducing the impact of the air knife on ceramic diffusion and thus reducing ceramic diffusion.
[0004] The patent (CN202121482425) improves the design of the ceramic slurry gasket by changing the structure of the gasket slurry and the ceramic outlet to create a height difference between the slurry and the ceramic slurry outlet. The ceramic slurry outlet is higher than the slurry outlet, which avoids pressure conflict in the horizontal direction and thus reduces ceramic diffusion.
[0005] The patent (CN202322192734) modifies the structure of the upper air nozzle of the coating machine by adding baffles on both sides of the upper air nozzle to prevent the air knife from blowing directly onto the ceramic, thereby reducing ceramic diffusion.
[0006] Problems identified: After the improvement of the ceramic coating gasket, the horizontal pressure between the slurry and the ceramic at the mold head does not interfere with each other, but the wet film still has a diffusion problem after entering the oven due to the influence of the air knife; after modifying the structure of the air nozzle on the coating machine, the baffle structure may cause uneven drying of the material at the edge.
[0007] Therefore, it is necessary to propose a simple and stable method for controlling the diffusion of ceramic slurry.
[0008] In view of this, the present invention is hereby proposed. Summary of the Invention
[0009] The first objective of this invention is to provide a UV-cured ceramic slurry for battery electrodes to solve the aforementioned technical problems.
[0010] The second objective of this invention is to provide a method for preparing the above-mentioned UV-cured ceramic slurry for battery electrodes.
[0011] A third objective of this invention is to provide a method for preparing battery electrodes.
[0012] To achieve the above objectives, the following technical solution is adopted:
[0013] In a first aspect, the present invention provides a UV-curable ceramic slurry for battery electrodes, comprising, by mass percentage: 28.05%-29.55% ceramic filler, 4.72%-5.07% polyvinylidene fluoride (PVDF), 0.88%-1.05% UV-curable adhesive, with the balance being solvent;
[0014] By weight percentage, the UV-curable adhesive comprises: 30%-40% active monomers, 2%-3% photoinitiator, and the balance being polyurethane acrylate;
[0015] The active monomers are butyl acrylate (BA) and methyl methacrylate (MMA), with a mass ratio of butyl acrylate to methyl methacrylate of 18:6-19:5.
[0016] As a further technical solution, the solvent includes N-methylpyrrolidone (NMP).
[0017] As a further technical solution, the photoinitiator includes 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO).
[0018] As a further technical solution, the UV-curable adhesive also includes a stabilizer with a mass ratio of 0.1%-0.25%.
[0019] As a further technical solution, the stabilizer includes hydroquinone (HQ).
[0020] Secondly, the present invention provides a method for preparing the above-mentioned UV-cured ceramic slurry for battery electrodes, wherein ceramic filler, polyvinylidene fluoride, UV curing adhesive and solvent are mixed and dispersed to prepare the UV-cured ceramic slurry for battery electrodes.
[0021] As a further technical solution, the mixing and dispersion process also includes defoaming treatment of the UV-cured ceramic slurry for battery electrodes.
[0022] Thirdly, the present invention provides a method for preparing a battery electrode, comprising the following steps:
[0023] The battery electrode is prepared by coating the current collector with electrode slurry and the above-mentioned UV-cured ceramic slurry for battery electrodes, and then sequentially undergoing photocuring and drying.
[0024] As a further technical solution, the photocuring method includes ultraviolet light irradiation;
[0025] The ultraviolet light has a wavelength of 250-420 nm and an energy density of 600-1000 mJ / cm². 2 .
[0026] As a further technical solution, the battery electrode is coated on both sides of the electrode slurry with UV-cured ceramic slurry.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1) Fast setting: Utilizing UV surface curing film-forming technology, the surface curing of ceramic slurry can be completed within 3 seconds. The ceramic setting can be completed before or in the early stage of oven curing, which can effectively solve the problem of ceramic diffusion.
[0029] 2) Good air permeability: The formula is reasonably designed to effectively prevent appearance problems such as pinholes and foil leakage during the complete drying process of ceramic slurry.
[0030] 3) Good weather resistance: The cured film can exist stably in the electrolyte.
[0031] 4) High stability: The ceramic shaping quality and rate during the coating process are related to the UV lamp power and UV adhesive content, but are independent of the coating process parameters and are close to constant, resulting in good stability.
[0032] 5) Low cost: Compared with conventional formulas and coating equipment, only a small amount of UV curing adhesive needs to be added to the ceramic slurry, and a certain length of UV lamp needs to be added to the coating machine. This solves the ceramic diffusion problem at a low cost and saves manpower and resources. Attached Figure Description
[0033] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0034] Figure 1 This is a schematic diagram illustrating the implementation of the UV-cured ceramic slurry of the present invention;
[0035] Figure 2 This is a schematic diagram of the electrode structure.
[0036] Icons: 1-Substrate; 2-Back roller; 3-Die head; 4-Ceramic edge; 5-UV lamp; 6-Electrode tab; 7-Active material coating. Detailed Implementation
[0037] The embodiments and examples of the present invention will be described in detail below. However, those skilled in the art will understand that the following embodiments and examples are for illustrative purposes only and should not be considered as limiting the scope of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Unless otherwise specified, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0038] In a first aspect, the present invention provides a UV-curable ceramic slurry for battery electrodes, comprising, by mass percentage: 28.05%-29.55% ceramic filler, 4.72%-5.07% polyvinylidene fluoride, 0.88%-1.05% UV-curable adhesive, with the balance being solvent;
[0039] By weight percentage, the UV-curable adhesive comprises: 30%-40% active monomers, 2%-3% photoinitiator, and the balance being polyurethane acrylate;
[0040] The active monomers are butyl acrylate and methyl methacrylate, with a mass ratio of butyl acrylate to methyl methacrylate of 18:6-19:5.
[0041] The UV-cured ceramic slurry for battery electrodes provided by this invention uses a UV lamp to rapidly cure a breathable UV adhesive film on the ceramic surface before the ceramic slurry enters the oven. This rapid curing of the ceramic slurry with this film ensures that the shaped ceramic is unaffected by other coating parameters during coating, thus solving the diffusion problem between the ceramic slurry and the active material slurry.
[0042] The UV-cured ceramic slurry for battery electrodes provided by this invention has good chemical weather resistance, and the cured film can exist stably in the electrolyte; it has good air permeability, which effectively prevents appearance problems such as pinholes and foil leakage during the complete drying process of the ceramic slurry; and it has a fast film formation speed, which can better adapt to the fast production rhythm of coating.
[0043] In some alternative embodiments, the solvent includes, but is not limited to, N-methylpyrrolidone, or other solvents well known to those skilled in the art.
[0044] In some alternative embodiments, the photoinitiator includes, but is not limited to, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, or other photoinitiators well known to those skilled in the art.
[0045] In some optional embodiments, the UV-curable adhesive also includes a stabilizer, the mass percentage of which may be, for example, but is not limited to, 0.1%, 0.2%, or 0.25%.
[0046] In some alternative embodiments, the stabilizer includes, but is not limited to, hydroquinone.
[0047] By adding stabilizers, the reactivity of the UV adhesive is reduced, its storage capacity is improved, and the slurry is prevented from curing due to environmental factors before coating.
[0048] Secondly, the present invention provides a method for preparing the above-mentioned UV-cured ceramic slurry for battery electrodes, wherein ceramic filler, polyvinylidene fluoride, UV curing adhesive and solvent are mixed and dispersed to prepare the UV-cured ceramic slurry for battery electrodes.
[0049] The preparation method is simple and convenient.
[0050] In some alternative embodiments, the mixing and dispersion process further includes defoaming the UV-cured ceramic slurry for battery electrodes.
[0051] This invention does not impose specific limitations on the defoaming method; for example, defoaming can be performed by vacuuming.
[0052] Thirdly, the present invention provides a method for preparing a battery electrode, comprising the following steps:
[0053] The battery electrode is prepared by coating the current collector with electrode slurry and the above-mentioned UV-cured ceramic slurry for battery electrodes, and then sequentially undergoing photocuring and drying.
[0054] The electrode preparation method provided by this invention enables the ceramic slurry to be quickly shaped before entering the oven, greatly reducing glue overflow, and reducing the risk of cracking during the oven preheating stage by baking at a low temperature, thereby improving product yield.
[0055] In some alternative embodiments, the photocuring method includes ultraviolet light irradiation;
[0056] The ultraviolet light has a wavelength of 250-420 nm and an energy density of 600-1000 mJ / cm². 2 .
[0057] In some alternative embodiments, the battery electrode is coated on both sides of the electrode paste with a UV-cured ceramic paste.
[0058] The present invention will be further illustrated below with specific embodiments. However, it should be understood that these embodiments are merely for the purpose of more detailed illustration and should not be construed as limiting the present invention in any way.
[0059] Example 1
[0060] A UV-curable ceramic slurry for battery electrodes comprises, by weight percentage: 29.05% ceramic filler (nano-ceramic powder), 4.9% polyvinylidene fluoride, 1.05% UV-curable adhesive, and the balance being N-methylpyrrolidone.
[0061] The UV-curable adhesive comprises, by weight percentage: 35% active monomers (butyl acrylate and methyl methacrylate in a mass ratio of 18:6), 2.5% 2,4,6-trimethylbenzoyl diphenylphosphine oxide, 0.2% hydroquinone, and the balance being polyurethane acrylate.
[0062] The preparation method is as follows:
[0063] Preparation of adhesive solution: Stir at 30 rpm, add some pre-dissolved TPO and HQ in NMP, the remaining NMP, polyurethane acrylate, active monomer, and PVDF. After adding, set the dispersion speed to 15 m / s and stir for 60 min. After stirring, bubbles will appear. Then, apply a vacuum of -85 kPa for 30 min.
[0064] Ceramic slurry preparation: Stir at 30 rpm, add nano-ceramic slurry in batches of 50%, 30%, and 20%, disperse at a linear velocity of 15 m / s for 20 min after each addition, disperse for 160 min for the last time, and then apply a vacuum of -85 kPa for 60 min after stirring.
[0065] Example 2
[0066] A UV-curable ceramic slurry for battery electrodes comprises, by weight percentage: 28.05% ceramic filler (nano-ceramic powder), 4.72% polyvinylidene fluoride, 0.95% UV-curable adhesive, and the balance being N-methylpyrrolidone.
[0067] The UV-curable adhesive comprises, by weight percentage: 30% active monomers (butyl acrylate and methyl methacrylate in a mass ratio of 18.5:5.5), 2% 2,4,6-trimethylbenzoyl diphenylphosphine oxide, 0.1% hydroquinone, and the balance being polyurethane acrylate.
[0068] The preparation method is the same as in Example 1.
[0069] Example 3
[0070] A UV-curable ceramic slurry for battery electrodes comprises, by weight percentage: 29.55% ceramic filler (nano-ceramic powder), 5.07% polyvinylidene fluoride, 1.05% UV-curable adhesive, and the balance being N-methylpyrrolidone.
[0071] By weight percentage, the UV-curable adhesive comprises: 40% active monomers (butyl acrylate and methyl methacrylate in a mass ratio of 18:6), 3% 2,4,6-trimethylbenzoyl diphenylphosphine oxide, 0.25% hydroquinone, and the balance being polyurethane acrylate.
[0072] The preparation method is the same as in Example 1.
[0073] Comparative Example 1
[0074] The difference from Example 1 is that no UV-curing adhesive is added.
[0075] Comparative Example 2
[0076] The difference from Example 1 is that the mass ratio of butyl acrylate to methyl methacrylate is 17:7.
[0077] Example 4
[0078] The difference from Example 1 is that the mass ratio of butyl acrylate to methyl methacrylate is 19:5.
[0079] Comparative Example 3
[0080] The difference from Example 1 is that the mass ratio of butyl acrylate to methyl methacrylate is 16:8.
[0081] Comparative Example 4
[0082] The difference from Example 1 is that the mass ratio of butyl acrylate to methyl methacrylate is 20:4.
[0083] Comparative Example 5
[0084] The difference from Example 1 is that the amount of UV-curable adhesive used is 1.23%.
[0085] Example 5
[0086] The difference from Example 1 is that the amount of UV-curable adhesive used is 0.88%.
[0087] Comparative Example 6
[0088] The difference from Example 1 is that the amount of UV-curable adhesive used is 5%.
[0089] Comparative Example 7
[0090] The difference from Example 1 is that the amount of UV-curable adhesive used is 2%.
[0091] Experimental Example 1
[0092] The electrode slurry (93.70% active material (lithium iron phosphate), 3.24% adhesive (polyvinylidene fluoride), 0.57% dispersant (polyvinylpyrrolidone), 0.57% conductive paste (carbon nanotubes), and 1.92% conductive agent (carbon black); solvent is NMP (N-methylpyrrolidone)) and the UV-cured ceramic slurry for battery electrodes of the above examples or comparative examples are coated on the current collector. The specific steps are as follows:
[0093] The ceramic slurry is transferred to a coating tank, and then coated onto the substrate 1 conveyed by the back roller 2 using a die 3 via extrusion coating. The ceramic is coated on both sides of the active slurry, such as... Figure 1 The coated ceramic is then transported to the working area of the UV lamp (250-420nm, energy density 600-1000mJ / cm²). 2 Under ultraviolet light irradiation, the UV adhesive on the surface of the ceramic slurry is initiated by the ultraviolet light, completing the surface film formation and shaping of the ceramic. After shaping, the ceramic slurry and the active slurry are put into a coating oven for thorough drying, resulting in a positive electrode sheet without ceramic diffusion. The structure of the positive electrode sheet is as follows: Figure 2 As shown, the active material coating 7 is located in the middle, with ceramic edge 4 and electrode tab 6 on both sides.
[0094] The prepared electrodes were subjected to the following tests:
[0095] 1) Appearance: Visually inspect the surface quality of the ceramic surface after film formation, measure the number of pinholes per unit length, and classify them according to severity, A1, A2, A3, A4, A5, which are progressively more severe, with A1 having no pinholes.
[0096] 2) Whether ceramic diffusion occurs: Prepare a low-concentration ceramic slurry, measure the diffusion width of the cured ceramic, and classify it according to the severity. B1, B2, B3, B4, and B5 are progressively more severe, while B1 has no diffusion.
[0097] 3) Electrolyte Immersion: After curing and drying, the ceramic is immersed in an electrolyte solution for 48 hours. Observe whether the outer film swells, peels off, or changes color. The electrolyte solution, by mass fraction, consists of: solvent (30% ethylene carbonate, 40% methyl ethyl carbonate, 5% propylene carbonate, 25% diethyl carbonate), lithium hexafluorophosphate (1.2 mol / L), and additives (0.5% lithium difluorosulfonate, 1.8% ethylene carbonate).
[0098] 4) Ceramic flexibility: The ceramic strip electrode with a width of 2cm is made. The electrode uses a cylinder with a diameter of 5cm. The winding tension is 100N to simulate the deformation of the electrode during the processing. The ceramic is visually observed to see if it cracks or falls off after winding.
[0099] The results are shown in Tables 1 and 2.
[0100] Table 1
[0101]
[0102] During the adjustment of the ratio of soft monomer (BA) and hard monomer (MMA), the soft monomer can improve the adhesion and flexibility of the adhesive, but it will reduce the density of the film; the hard monomer can improve the density and hardness of the film, but an excessively high ratio will reduce the toughness of the film. As shown in the examples and comparative examples, the optimal active monomer ratio is BA:MMA between 18:6 and 19:5. For ease of preparation, the optimal BA:MMA ratio is taken as 18:6. A suitable active monomer ratio can maintain good flexibility, prevent detachment, and prevent cracking during battery processing and in the battery electrolyte.
[0103] Table 2
[0104]
[0105]
[0106] During the adjustment of UV adhesive content, due to the unconventional curing of UV adhesive, after the surface cures and forms a film, the solvent inside evaporates during the subsequent drying process. Excessive film thickness leads to decreased air permeability, resulting in numerous pinholes, and in severe cases, foil leakage. Insufficient UV adhesive results in unstable curing and discontinuous film formation. As shown in the examples and comparative examples, the optimal UV adhesive concentration is between 0.88% and 1.05%, with 1.05% being the preferred optimal concentration. With the appropriate UV adhesive content, the surface film thickness is suitable and continuous, and there are no visual abnormalities after the ceramic slurry is completely dried.
[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A UV-cured ceramic slurry for battery electrodes, characterized in that, By weight percentage, it includes: 28.05%-29.55% ceramic filler, 4.72%-5.07% polyvinylidene fluoride, 0.88%-1.05% UV-curable adhesive, with the balance being solvent; By weight percentage, the UV-curable adhesive comprises: 30%-40% active monomers, 2%-3% photoinitiator, and the balance being polyurethane acrylate; The active monomers are butyl acrylate and methyl methacrylate, and the mass ratio of butyl acrylate to methyl methacrylate is 18:6-19:
5. The battery electrode is coated on both sides of the electrode paste with UV-cured ceramic paste.
2. The UV-cured ceramic slurry for battery electrodes according to claim 1, characterized in that, The solvent includes N-methylpyrrolidone.
3. The UV-cured ceramic slurry for battery electrodes according to claim 1, characterized in that, The photoinitiator includes 2,4,6-trimethylbenzoyldiphenylphosphine oxide.
4. The UV-cured ceramic slurry for battery electrodes according to claim 1, characterized in that, The UV-curable adhesive also includes a stabilizer at a mass ratio of 0.1%-0.25%.
5. The UV-cured ceramic slurry for battery electrodes according to claim 4, characterized in that, The stabilizer includes hydroquinone.
6. The method for preparing the UV-cured ceramic slurry for battery electrodes according to any one of claims 1-5, characterized in that, A UV-curable ceramic slurry for battery electrodes is prepared by mixing and dispersing ceramic filler, polyvinylidene fluoride, UV-curable adhesive and solvent.
7. The preparation method according to claim 6, characterized in that, The mixing and dispersion process also includes defoaming treatment of the UV-cured ceramic slurry for battery electrodes.
8. A method for preparing a battery electrode, characterized in that, Includes the following steps: A battery electrode is prepared by coating an electrode slurry and a UV-cured ceramic slurry for battery electrodes according to any one of claims 1-5 onto a current collector, followed by sequential photocuring and drying.
9. The preparation method according to claim 8, characterized in that, The photocuring method includes ultraviolet light irradiation; The ultraviolet light has a wavelength of 250-420 nm and an energy density of 600-1000 mJ / cm². 2 .
10. The preparation method according to claim 8, characterized in that, The battery electrode is coated on both sides of the electrode paste with UV-cured ceramic paste.
Citation Information
Patent Citations
Coated ceramic gasket
CN216137597U
Mechanism for improving coating of ceramic sol
CN220919826U
Electrode paste for lithium secondary battery, electrode and lithium secondary battery
CN106848209A
Lithium ion battery pole piece coated with ceramic paste and preparation process thereof
CN107681117A